PENGARUH LEVERAGE, INTELLECTUAL CAPITAL DAN OWNERSHIP STRUCTURE TERHADAP KINERJA KEUANGAN - Putri, Lusi Amanda; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis This research is meant to examine some factors which influene the company financial statement on manufacturing companies which are listed in Indonesia Stock Echange. The variables in this research are leverage, intellectual capital, managerial ownership, and institusional ownership. This research is a quantitative research and the research population is manufacturing companies which are listed in Indonesia Stock Echange in 2013-2015 periods. The sample collection technique has been done by using purposive sampling and 12 companies (36 firm years) which have met the criteria have been selected as the research samples. The analysis technique has been done by using multiple linear regression analysis and the SPSS 23. This result of the research shows that leverage give negative and significant influence to the company financial statement, intellectual capital and managerial ownership give positive and insignificant influence to the company financial statement whereas institusional ownership give positive and significant influence to the company financial statement.Keywords: Financial statement, leverage, intellectual capital, ownership structure